2022
DOI: 10.1186/s13102-022-00566-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of two exercise programs on health-related fitness, quality of life and exercise enjoyment in adults with visual impairment: a randomized crossover trial

Abstract: Background So far there is no study comparing two distinct exercise interventions in people with visual impairment. This study aimed to evaluate the effects of two exercise programs on health-related fitness, quality of life, and exercise enjoyment in people with visual impairment. Methods Two exercise interventions were conducted: sports (i.e., Goalball, Football 5-a-side and Martial Arts) and functional training (i.e., Bodyweight exercises). Phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
0
0
Order By: Relevance
“…Their review included only randomized controlled trials and pre-post studies that provided exercise intervention for adults with visual impairment and reported physical outcomes. However, there have been studies to identify quality of life, mental health, and psychosocial benefits as exercise outcomes for adults with visual impairment (Bao et al, 2021;da Silva et al, 2022;McCarthy et al, 2018). Different research designs have also been conducted to investigate the influence of exercise interventions (de Jong et al, 2021;Hackney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Their review included only randomized controlled trials and pre-post studies that provided exercise intervention for adults with visual impairment and reported physical outcomes. However, there have been studies to identify quality of life, mental health, and psychosocial benefits as exercise outcomes for adults with visual impairment (Bao et al, 2021;da Silva et al, 2022;McCarthy et al, 2018). Different research designs have also been conducted to investigate the influence of exercise interventions (de Jong et al, 2021;Hackney et al, 2015).…”
Section: Introductionmentioning
confidence: 99%